ECONOMIC ANALYSIS AND PRODUCTION OF CORN (Zea mays L.) ASSOCIATED WITH MUCUNA (Stizolobiumaterrimum) IN DIRECT SOWING AND TWO SYSTEMS OF NITROGEN FERTILIZATION - González Osorio, Betty (2008)
A study with the purpose of observing the profitability and the effect of the dose of nitrous fertilization and the inserted of S. aterrimum in the development and production of the INIAP H-551 hybrid corn planted in two places was carried out. It was found that the dose 200 kg ha-1 of urea fractioned in two applications obtained the best plant development, yield of the corn and the biggest relationship cost/profit. When relating the production of biomass with the applied contents of the fertilization it was recorder that to smaller dose of N bigger covering of S. aterrimun; and smaller overgrowth incidence; the nodulation presented the same effect to a smaller content in the soil of N, Ca, Zn, Fe and Mo, the production of nodules increases. The dose of 100 kg ha-1 of urea fractioned in two applications presented the best marginal rate of return in physical terms the balance point was at 3164.40 kg ha-1, being observed in both cases new production alternatives to improve and to recover soils and the productivity of the corn cultivation.